Prophylactic treatment of Glycyrrhiza glabra mitigates COVID-19 pathology through inhibition of pro-inflammatory cytokines in the hamster model and NETosis - Rizvi, Zaigham Abbas; Babele, Prabhakar; Sadhu, Srikanth; Madan, Upasna; Tripathy, Manas Ranjan; Goswami, Sandeep; Mani, Shailendra; Kumar, Sachin; Awasthi, Amit; Dikshit, Madhu (Frontiers in Immunology, 2022)
Severe coronavirus disease (COVID-19) is accompanied by acute respiratory distress syndrome and pulmonary pathology, and is presented mostly with an inflammatory cytokine release, a dysregulated immune response, a skewed neutrophil/lymphocyte ratio, and a hypercoagulable state. Though vaccinations have proved effective in reducing the COVID-19-related mortality, the limitation of the use of vaccine against immunocompromised individuals, those with comorbidity, and emerging variants remains a concern. In the current study, we investigate for the first time the efficacy of the Glycyrrhiza glabra (GG) extract, a potent immunomodulator, against SARS-CoV-2 infection in hamsters. Prophylactic treatment with GG showed protection against loss in body weight and a 35%–40% decrease in lung viral load along with reduced lung pathology in the hamster model. Remarkably, GG reduced the mRNA expression of pro-inflammatory cytokines and plasminogen activator inhibitor-1 (PAI-1). In vitro, GG acted as a potent immunomodulator by reducing Th2 and Th17 differentiation and IL-4 and IL-17A cytokine production. In addition, GG also showed robust potential to suppress ROS, mtROS, and NET generation in a concentration-dependent manner in both human polymorphonuclear neutrophils (PMNs) and murine bone marrow-derived neutrophils (BMDNs). Taken together, we provide evidence for the protective efficacy of GG against COVID-19 and its putative mechanistic insight through its immunomodulatory properties. Our study provides the proof of concept for GG efficacy against SARS-CoV-2 using a hamster model and opens the path for further studies aimed at identifying the active ingredients of GG and its efficacy in COVID-19 clinical cases.